2020
DOI: 10.1111/1744-9987.13477
|View full text |Cite
|
Sign up to set email alerts
|

Use of double filtration plasmapheresis for the treatment of acquired thrombocytopenic thrombotic purpura

Abstract: Double filtration plasmapheresis (DFPP) could be an alternative method to simple plasma exchange plasmapheresis in the treatment of acquired thrombotic thrombocytopenic purpura (aTTP). In a retrospective single center case series, we studied clinical presentation, management care, and prognosis of aTTP patients from our academic center treated with DFPP and IV infusion of fresh frozen plasma (FFP) between 2009 and 2018. Nine patients were included for 11 episodes. Median age was 38 years old (IQR 26‐53) with 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(58 reference statements)
0
9
1
Order By: Relevance
“…DFPP removes the immunoglobulin fraction from the serum selectively [40]. DFPP has been used for several indications such as hyperacute rejection in ABO-incompatible kidney transplantation, and in the treatment of anti-neutrophil cytoplasmic antibody-associated vasculitis with severe kidney dysfunction [41,42]. In the literature, DFPP has not yet been performed in sepsis and ARDS, and also in COVID-19 yet, and how it will affect the course of the disease is not known.…”
Section: Double-filtration Plasmapheresis (Dfpp)mentioning
confidence: 99%
“…DFPP removes the immunoglobulin fraction from the serum selectively [40]. DFPP has been used for several indications such as hyperacute rejection in ABO-incompatible kidney transplantation, and in the treatment of anti-neutrophil cytoplasmic antibody-associated vasculitis with severe kidney dysfunction [41,42]. In the literature, DFPP has not yet been performed in sepsis and ARDS, and also in COVID-19 yet, and how it will affect the course of the disease is not known.…”
Section: Double-filtration Plasmapheresis (Dfpp)mentioning
confidence: 99%
“…Chauvel et al reported DFPP for 11 episodes of 9 TTP patients. 9 Remission was achieved in 9 cases (9/ 11 = 82%) and the author stated remission rate…”
Section: Clinical Features Of Dfppmentioning
confidence: 94%
“…However, recently several articles were published using DFPP in TTP and ANCA‐associated vasculitis. Chauvel et al reported DFPP for 11 episodes of 9 TTP patients 9 . Remission was achieved in 9 cases (9/11 = 82%) and the author stated remission rate comparable to PE.…”
Section: Clinical Features Of Dfppmentioning
confidence: 95%
“…Among the various types of plasmapheresis, s imple nonselective therapeutic plasmapheresis is, by definition, when all the collected plasma components (including albumin, clotting factors, and IGs) are discarded and replaced with some combinations of albumin, donor plasma, or colloids 3 . This can be performed by centrifuging to separate the cells and plasma according to their density (removing all plasma components including very large molecules like chylomicrons which may sometimes reach 1000 nm) or, alternatively, by filtration through a plasma membrane separator (pore size 300‐500 nm) with similar efficacy in most situations 4,5 . However, the filtration fraction of plasma differs according to the method.…”
Section: Introductionmentioning
confidence: 99%
“…3 This can be performed by centrifuging to separate the cells and plasma according to their density (removing all plasma components including very large molecules like chylomicrons which may sometimes reach 1000 nm) or, alternatively, by filtration through a plasma membrane separator (pore size 300-500 nm) with similar efficacy in most situations. 4,5 However, the filtration fraction of plasma differs according to the method. It is around 60% to 80% for centrifugal plasmapheresis and around 20% to 25% for filtration.…”
Section: Introductionmentioning
confidence: 99%